Analysis of the Potential Threat of Indonesian Foreign Terrorist Fighters in Syria to Indonesia - Parmadi, Varadito; Daryanto, Eko; Riyanta, Stanislaus (GoAcademica Research & Publishing, 2024)
The movement of Foreign Terrorist Fighters (FTFs) in Syria has emerged as a global phenomenon, drawing serious attention from numerous countries due to its significant scale. Indonesia is among the nations contributing to the movement of FTFs in this context. A critical aspect currently under scrutiny is the discourse around their repatriation to Indonesia. Therefore, a key component that must be considered is the potential threat these individuals pose upon returning to Indonesia. To address this, the study employs a qualitative approach, gathering data through literature reviews and interviews with stakeholders directly involved with Indonesian FTFs. The research provides an analysis of the various potential threats posed by these FTFs upon their return to Indonesia, based on a review of literature and factual data regarding the actions previously undertaken by FTFs in Indonesia.